Assessment of the In Vivo Antioxidant Activity of an Anthocyanin-Rich Bilberry Extract Using the Caenorhabditis elegans Model - Ana M. González-Paramás; Virginia Brighenti; Laura Bertoni; Laura Marcelloni; Begoña Ayuda-Durán; Susana González-Manzano; Federica Pellati; Celestino Santos-Buelga (MDPI AG, 2020)
Anthocyanins have been associated with several health benefits, although the responsible mechanisms are not well established yet. In the present study, an anthocyanin-rich extract from bilberry (Vaccinium myrtillus L.) was tested in order to evaluate its capacity to modulate reactive oxygen species (ROS) production and resistance to thermally induced oxidative stress, using the nematode Caenorhabditis elegans as an in vivo model. The assays were carried out with the wild-type N2 strain and the mutant strains daf-16(mu86) I and hsf-1(sy441), which were grown in the presence of two anthocyanin extract concentrations (5 and 10 μg/mL in the culture medium) and further subjected to thermal stress. The treatment with the anthocyanin extract at 5 μg/mL showed protective effects on the accumulation of ROS and increased thermal resistance in C. elegans, both in stressed and non-stressed young and aged worms. However, detrimental effects were observed in nematodes treated with 10 μg/mL, leading to a higher worm mortality rate compared to controls, which was interpreted as a hormetic response. These findings suggested that the effects of the bilberry extract on C. elegans might not rely on its direct antioxidant capacity, but other mechanisms could also be involved. Additional assays were performed in two mutant strains with loss-of-function for DAF-16 (abnormal DAuer Formation factor 16) and HSF-1 (Heat Shock Factor 1) transcription factors, which act downstream of the insulin/insulin like growth factor-1 (IGF-1) signaling pathway. The results indicated that the modulation of these factors could be behind the improvement in the resistance against thermal stress produced by bilberry anthocyanins in young individuals, whereas they do not totally explain the effects produced in worms in the post-reproductive development stage. Further experiments are needed to continue uncovering the mechanisms behind the biological effects of anthocyanins in living organisms, as well as to establish whether they fall within the hormesis concept.